Comparative Study of Physico-Chemical Parameters of Karra, Rapti and Samari River Water of Hetauda - Pahadi, Prakash; Adhikari, Solar; Kharel, Dipak; Lamichhane, Chiranjivi; Chaube, Srijesh; Shrestha, Madhusudan (International Research Journal of MMC, 2023)
The genesis of civilization was directly linked with the quality of water and its resource. Any degradation in the water quality will hamper the development of the society because of its direct impact on human health. Therefore the physical and chemical parameters of the water have to be measured time to time to ensure its standard limit. This research aimed to find out the chemical and physical status of the three rivers located inside as well as at the periphery of Hetauda sub-metropolitan city in Makawanpur district. During the mid-week of January 2023, water sample from Karra, Rapti and Samari Rivers were collected in order to compare and study their Physico-Chemical Parameters. The physical parameters like odour, color, pH value and temperature were measured on site while other physical values such as conductivity, and Total Dissolved Solids (TDS) along with the corresponding chemical parameters like hardness, alkalinity and chemical oxygen demand (COD) were measured at chemistry laboratory in Makawanpur Multiple Campus. The test suggested that the water from these rivers were unfit for direct drinking.